Rain in Plural : Poems - Sze-Lorrain, Fiona (Book collections on Project MUSE., 2020)
"Description A highly anticipated new collection from a poet whose previous book was a finalist for the Los Angeles Times Book Prize Rain in Plural is the much-anticipated fourth collection of poetry by Fiona Sze-Lorrain, who has been praised by The Rumpus as "a master of musicality and enlightening allusions." In the wholly original world of these new poems, Sze-Lorrain addresses both private narratives and the overexposed discourse of the polis , using silence and montage, lyric and antilyric, to envision what she calls "creating between liberties." With a moral precision embracing us without eschewing I , she rethinks questions of citizenship, the selections of sensory memory, and, by extension, the tether of word and image to the actual. She writes, "I accept the truth in newspapers / by holding the murder of my friends against my chest. // To each weather forecast I give thanks: / merci for every outdated // dusk/dawn." Agrippina the Younger, Franz Kafka, Bob Dylan, a butoh performance, an unnamed Raku tea bowl-each has a place here. Made whole by time and its alteration in timelessness, synchrony, coincidences, and accidents, Rain in Plural beautifully reveals an elegiac yet ever-evolving inner life"--